Refleksi Performa Pelayanan Administrasi Di Tingkat Kelurahan Atau Desa Gunung Halu - Ageng Saepudin Kanda; Muhammad S Algias (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Administrative services at the sub-district or village level are one of the public services that are very important for the community. This administrative service includes various types of certificates, such as birth certificates, death certificates and resident mutation letters. This research uses a qualitative method with a descriptive approach, with library study research techniques and field studies with observation, interviews and documentation to collect data. Other research shows that analysis of the quality of administrative services at the sub-district office of Gunung Halu Regency can be carried out using quantitative methods with techniques. questionnaire data collection. The results of the research show that the quality of administrative services at the sub-district office of Gunung Halu Regency still needs to be improved. In technical guidance, village officials are provided with knowledge and skills in financial management and village administration.